1988
DOI: 10.1007/bf00455663
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioidomycosis in nude mice: Presence of filamentous forms of the fungus

Abstract: Congenitally athymic nude mice (nu/nu) and their phenotypically normal littermates (nu/+) were intraperitoneally infected with yeast cells of a strain of Paracoccidioides brasiliensis. The nude mice developed a severe and generalized infection with an intense parasitism of several organs, accompanied by a low-grade of tissue reaction. The lesions were characterized by abundant yeast-like cells of the fungus, and in some animals, numerous hyphal forms could be well visualized. In control animals, infection was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this case, nude mice are more severely affected than normal animals by infectious pathogens which are cleared by the cell-mediated immune mechanisms. This group contains C. neoJormans [10], B. dermatitidis [11], C. immitis [12], P. brasiliensis [13] and H. capsulatum [14]. In the present study, nude mice showed a higher susceptibility to infection with P. marneffei compared with euthymic mice.…”
Section: P Marneffei Is An Important Opportunistic Infectiousmentioning
confidence: 58%
See 2 more Smart Citations
“…In this case, nude mice are more severely affected than normal animals by infectious pathogens which are cleared by the cell-mediated immune mechanisms. This group contains C. neoJormans [10], B. dermatitidis [11], C. immitis [12], P. brasiliensis [13] and H. capsulatum [14]. In the present study, nude mice showed a higher susceptibility to infection with P. marneffei compared with euthymic mice.…”
Section: P Marneffei Is An Important Opportunistic Infectiousmentioning
confidence: 58%
“…To confirm our hypothesis, we used congenitally athymic nude mice, which are known to have deficient cell-mediated immunity and impaired T cell-dependent antibody production [21]. These animals have been used in the past to study the pathological effects of a variety of infectious agents [10][11][12][13][14]22,23]. Previous studies demonstrated that the resistance to fungal infection involves two different mechanisms.…”
Section: P Marneffei Is An Important Opportunistic Infectiousmentioning
confidence: 64%
See 1 more Smart Citation
“…A low inoculum in the 5 x 102 range causes a [8] concluded that the virulence of P. brasiliensis may be attenuated or lost in subcultures carried out for long periods of time. Considering the times of isolation and continued preservation under mineral oil of the strains studied here, and the possibility of in vivo filamentation of P. brasiliensis reported by Londero et al [9] for man and by Kerr et al [10] for nude mice, we suggest that some factors regulating the mechanism of dimorphism and virulence still need elucidation.…”
Section: Introductionmentioning
confidence: 84%